Obtenção, purificação e caracterização de β1,3-Glucanase de Moniliophthora Perniciosa Aimephillipsmora (Singer) - Sena, Amanda Reges de (2010)
The fungus Moniliophthora perniciousa causes a great reduction in production of cocoa crop since 1989 because is the agent causative of the disease known as witche’s broom. Among the enzymes involved in metabolism of the fungus, there is a β1,3glucanase, which has lysozyme activity and the group of chitinases,mwhich degrade polysaccharides such as βglucans and chitin, respectively. This work has the objective of purify, to characterize, determine the kinetic parameters and to study inhibitors on mycelial growth of Moniliophthora pernicious . In the optimization of production of β1,3glucanase was used five levels of yeast extract and three levels of fermentation time by Doehlert matrix. The predicted optimum values of inductor and fermentation time were 5.9 g/L and 13 days, respectively. The results showed three different glucanases isoforms (GLUI, GLUII and GLUIII) with purification factors of 4.33, 1.86 and 3.03, respectively. The enzyme exhibited an optimum catalytic activity at pH 5 and 40 ºC, and thermoestability at 60ºC. The activity was increased to 0.2 mol/L and 0.6 mol/L in the presence of NaCl and KCl, respectively. The enzyme extract obtained from the central point of the planning was used to verify the susceptibility of two Pseudozyma sp. to lysis. The experiment design showed that the best conditions to Pseudozyma sp. (CCMB 300) lyses were pH 4 and 20ºC and Pseudozyma sp. (CCMB 306) lysis were pH 5 and 40ºC. Looking for an alternative to controlling the witch’s broom, were tested extracts seven plant species (Marcetia latifolia, M. canescens, M. taxifolia, M. harley, M. formosa, Agave sisalana e Xanthium cavanillesii) at concentrations ranging from 250 to 4000 μg/mL. The butanolic extract from A. sisalana and the ethanolic extract from X. cavanillessi leaf were the most active against fungus tested with significant inhibition of 100% to 4000 μg/mL and 500 μg/mL, respectively. Results obtained by the measurements of MIC, indicate that the values are, respectively, 500 μg/mL for ethanol extract of the leaf and 2500 μg/mL for ethanolic extract of stem of X. cavanillesii.